Students’ Attitude Towards Their Peers With Disabilities: Case Of Gyumri Schools - Akopyan, Tigranui
This study aims to understand children's attitudes toward their peers with disabilities in the city of Gyumri (Armenia). As the inclusion of students with disabilities in regular schools has been increasingly promoted worldwide in the last few decades, starting from 2016, full (universal) inclusive education entered into force in Armenia, and children with and without disabilities are included in the classrooms in all regular schools in the country. Based on the new changes related to inclusive education, the research on children’s attitudes toward their peers with disabilities is valuable and essential.A narrative qualitative approach is used as a methodological basis of this study to uncover the attitudes of non-disabled students towards their peers with disabilities. Qualitative in-depth interviews with 60 students from inclusive schools in Gyumri have been conducted within one month. Analysis of the interviews was performed using the thematic analysis method. The findings suggest four essential categories of responses: Looking forward, Belief in overall inclusion, Pessimistic view, and Unfavorable conditions. Each topic is formulated based on themes that describe the interview's global and detailed expression and formulation. In general, it was found that both personal and environmental variables relate to the attitudes of students without disabilities, such as experience with inclusive education, knowledge about disability and social participation, and social inclusion of students with disabilities.
Keywords: Education